Range expansion and population growth of non‐native mountain goats in the Greater Yellowstone Area: Challenges for management. (6th March 2016) - Flesch, Elizabeth P.; Garrott, Robert A.; White, P. J.; Brimeyer, Doug; Courtemanch, Alyson B.; Cunningham, Julie A.; Dewey, Sarah R.; Fralick, Gary L.; Loveless, Karen; McWhirter, Doug E.; Miyasaki, Hollie; Pils, Andrew; et al.
ABSTRACT: Population growth and range expansion of nonnative species can potentially disrupt ecosystem function or add conservation value to an area, and evaluation of possible impacts can be a challenge for managers. Nonnative populations of mountain goats ( Oreamnos americanus ) are present in the Greater Yellowstone Area (GYA) in the U.S. states of Idaho, Montana, and Wyoming because of historical introduction events, but their population trend and range have not been assessed across the area. We used 6, 701 location records from 1947 to 2015 to map mountain goat distribution and evaluate, in a descriptive manner, range overlap with native bighorn sheep ( Ovis canadensis ). We analyzed 136 survey counts using the Exponential Growth State–Space model to estimate population trends and abundance. Mountain goats dispersed 50–85 km from introduction sites to occupy all mountain ranges in the northern GYA and 30–40 km to occupy new areas in the southern GYA. Mountain goat numbers increased in nearly all count units, with the strongest growth rates estimated in areas more recently colonized. Using moderate detection probability (0.70), we estimated approximately 2, 355 mountain goats in the GYA. Although not tested in our analysis, the gradual range expansion and population growth rates were consistent with density‐dependent processes observed in other introduced large herbivores and demonstrate that mountain goats can successfully disperse over unsuitable locales to colonize new areas. Therefore, we expect mountain goat populations will continue to expand into unoccupied mountain ranges that contain significant numbers of bighorn sheep unless specific management actions are implemented to address their population growth. © 2016 The Wildlife Society.